Critical Discourse Analysis on the Instagram Account Mubadalah.id from the Perspective of Islamic Feminism - Sitti Rohmah; Budi Suyanto (Journal of Feminism and Gender Studies, 2023)
This study aims to analyze the macro structure, super structure, and micro structure contained in the media text Mubilah.id. The research method used is descriptive qualitative method with Teun's perspective. A. Van Dijk. The data collection used in this study is the listening method with reading techniques and note taking techniques. The results of the data analysis in this study are (1) the macro structure depicts how the act of polygamy in Islam is not recommended; (2) the superstructure in the study shows that the data is preceded by the title, opening text, news content, and closing section; and (3) The micro structure in this study consists of semantics in which there is a background in the form of before marriage, details indicating media control or emphasis on decisions in an agreement made before marriage, the intent/implicature is that marital relations may not create domination of rights in one of them. between the two, and the presupposition that arises is that women have the full right to decide or refuse polygamy. Furthermore, the syntax which consists of coherence, cause and effect to get the dream marriage, namely by establishing communication by submitting conditions or prenuptial agreements and stylistics in the form of the right choice of words is marriage. All data contains views of Islamic feminism which are built not to favor only one gender. However, giving a broad view to glorify fellow human beings. Keywords : Acts of Violence, Agreement, Gender, Marriage, and Mubadalah.id